Prediksi Laju Infiltrasi Metode Flooding Ditinjau Dari Karakteristi Tanah pada Kawasan Banjir di Kota Balikpapan Tengah - Kiptiah, Mariatul (JST (Jurnal Sains Terapan), 2022)
Floods are the thiird highest natural disaster occurrence in Balikpapan City after landslides (38.36%) and fallen trees (35.85%). Flood locations experienced an increase in incidence, one of which was in Sumber Rejo Village, Central Balikpapan, Balikpapan City. In 2020 increased to 7 events (an increase of 25.71%). Central Balikpapan District is a flooded area that has a lot of land covered with morphological conditions located on a steep slope, having an area of 2,205 Km2. The high intensity of rainfall has caused some parts of this area to be affected by floods it can disrupt the activities of local residents. This study was conducted in a high-flood area, namely in the sub-district of Central Balikpapan, using the Horton, Holtan and Philip Method of analyse and the flooding method. Based on the result of the analysis and testing on the studies that have been carried out, the land cover for the measurement location of Land (TK), Angsana Tree (PA), Shurbs (SN), Jackfruit Tree (PN). Soil classification is sandy loam and clayey sand, and porosity category are low and medium. Analysis of the actual infiltration rate for location PN 8.52% cm/hour (slightly fast), SB 4.32 cm/hour and PA 2.55cm/hour (moderate) and TK 1.98 cm/hour (slightly slow). Horton’s model is suitable for use in this location because it can be applied to variants in land cover. The results of the analysis of the method starting at the 10th minute to the 180th minute still occurred inundation even though the inundation condition decreased. This shows that the four-measurement location in the flood of Balikpapan City have very small infiltration rates.